New paradigms of education applied to circuit design course - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2007)
The aim of this work is to report application of new paradigms of education to the Computer Aided Circuit Design Course offered in Electronics and Telecommunication Program of Technical Education Faculty of Marmara University. New paradigms of education, problem based learning, outcome based learning issues are discussed. Application of problem based learning principles to the Computer Aided Circuit Design Course is presented and obtained results are discussed.
Keywords: problem based learning; new paradigms of education; circuit design; simulation